Urban battle fields of South Asia : lessons learned from Sri Lanka, India, and Pakistan - Fair, C. Christine (Rand Corporation monograph series., 2004)
This study examines several case studies of sustained campaigns of urban terrorism perpetrated by various domestic groups in the countries of India, Pakistan and Sri Lanka. One focus of this research addresses the modus operandi of the militant outfits. It describes the tactics they employ, their targeting means and objectives, and the ways in which these groups have innovated and evolved over time. This report illuminates, where possible, links that militant groups forge with other such organizations within South Asia and beyond. This work also examines the ways in which the three states respond to the menace of urban terrorism. It explains how each state mobilizes its security apparatuses (military, paramilitary, police), intelligence agencies as well as legislative and judicial bodies to counter the emerging threats. Finally, this research identifies key insights from these country-specific case studies that may inform U.S. stability operations in the cities of Afghanistan, Iraq and elsewhere.